News Distribution Strategies for Social Media Engagement: A Case Study of Liputan6 SCTV - Pertiwi, Lale Sekar Idaman; Nur, Muhammad Jamiluddin; Riyayanatasya, YY Wima (JURNAL KOMUNIKASI INDONESIA, 2025)
The rapid advancement of digital technology has accelerated media convergence, positioning Instagram and YouTube as strategic platforms for visual and audiovisual news distribution in line with modern audience consumption patterns. This study examines Liputan 6 SCTV’s Instagram and YouTube distribution strategies and their impact on audience engagement, content reach, and news visibility in the digital media landscape. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documents. The findings indicate that Liputan 6SCTV’s content distribution strategies embody a multidimensional form of media convergence that integrates technological, editorial, and cultural aspects. Nine key strategies were identified: information speed, visual strength, time relevance, SEO optimization, adaptive formats, interactivity, persuasive Calls-to-Action (CTA), networked collaboration, and cross-platform integration. These strategies collectively enhance visibility, engagement, and brand identity while fostering active audience participation. The synergy between Instagram and YouTube illustrates a paradigm shift in journalism toward a collaborative, participatory model within the evolving digital media ecosystem. This study advances media convergence and digital journalism by showing how broadcast media use cross-platform strategies to enhance engagement and relevance.